WSPÓŁCZESNA POLSKA RELIGIJNOŚĆ W KONTEKŚCIE TEORII ANOMII R. K. MERTONA - Królikowska, Anna (Wydział Prawa i Administracji UAM, 2001)
Many quick changes, as a rule, do increase a possibility of anomie. Also, or even - especially, in the field of religiousness. After the period of transition the old model according to which „to be Pole is to be Catholic” still persists, but the new situation (in its political, economical, social and cultural aspects) has much influenced and changed Polish religiousness. Nowadays in Poland people is meeting an uneasy task to reconcile, on one hand, the requirements and standards of Polish traditional Catholic Church addressed to them as to worshippers, with the new reality and its demands - on the other. Individuals react using some adaptive strategies. In this paper an attempt to analyse Polish religiousness in context of R. K. Merton’s adaptive behavior typifying has been carried out. The aim and means have been assumed in the language of church religiousness. Only a few per cent of Polish society consequently accomplish the church model of religiousness in their Uves (conformity). It might be expected that other types of reactions can be classified correspondingly to other types of individual adaptive behaviors like innovation, ritualism, withdrawal, contestation, etc.
CONTEMPORARY POLISH RELIGIOUSNESS IN THE CONTEXT OF ROBERT MERTON’S ANOMIE THEORY